MENINGKATKAN KEMAMPUAN BERHITUNG 1-20 ANAK USIA 5-6 TAHUN MELALUI PERMAINAN BOLA ANGKA - Sulistyawati, Rina Rina (Jurnal CARE (Children Advisory Research and Education), 2023)
This study aims to improve the ability to count 1-20 in children aged 5-6 years through the object number ball game in group B students of Nur Alif Babelan Islamic Kindergarten Bekasi consisting of 4 boys and 8 girls. To obtain data using observation techniques. Types of Classroom Action Research (CAR) Kemmis Me Taggart model with two cycles each cycle there are 4 stages, namely observation, planning, implementation and observation/reflection. The results showed that the ability to count through the ball game of numbers in the initial observation / pre-cycle 40% category began to develop. After the first cycle, 60% of the children's categories developed as expected and after the second cycle, the average development of numeracy skills was 80%, the cognitive category developed very well.Keywords: Counting Ability, Number Ball Game